Implementasi Permainan Sederhana untuk Meningkatkan Keterampilan Passing Futsal di Ekstrakurikuler pada Siswa - Santoso, Nuruddin Priya Budi; Hartono, Soetanto (MAN Insan Cendekia Jambi, 2024)
The aim of this research is: to provide inspiration for teachers and improve futsal extracurricular activities, as well as being able to create maximum activities. Students are expected to be able to develop the ability to compose sentences better by passing in futsal through simple game methods. The research method applied is Classroom Action Research (PTK) which consists of two cycles. The following are the steps taken: (1) Planning stage, (2) Action implementation, (3) Observation, (4) Reflection on the results of the action. The data analysis technique applied uses descriptive statistics with a percentage approach. Based on the results of research on passing tests through simple games in extracurricular futsal at SDN Sabranglor, the average achievement in Cycle I was 61,867 with a percentage of 32%, and the average achievement in Cycle II was 82,667 with a percentage of 88%. These results can be concluded that there is an increase in passing skills using simple game methods in extracurricular futsal at SDN Sabranglor.